Economic Geography and Manufacturing Productivity in Africa : An Analysis of Firm Level Data - Elbadawi, Ibrahim (2012)
We compare samples of textiles and garments producers across groups of countries to find that, in general, productivity is far lower in Sub-Saharan Africa than it is in India. Indian manufacturers in turn are significantly less productive than their counterparts in Morocco, while producers in some SSA countries do match or exceed the Indian standard. The paper assesses the importance of geography as a possible factor in these gaps compared to such possible causes as trade policy and the quality of public institutions. It turns out that both institutions and trade policy are strong influences on country productivity averages. However, geography is also as powerful an influence in as far as it affects access to export markets and to input supplies.